Analisis Wacana Kritis Model Teun Van Dijk pada Kanal Youtube Ferry Irwandi Yang Berjudul “Salah Respon Pemerintah Soal Tiktok” - Abimanyu, Giovanni Dimas (Research Community for Critical Society and Environment, 2024)
The issue of e-commerce Tiktok Shop has been widely discussed lately due to the assumption that e-commerce Tiktok Shop is considered to violate regulations and is detrimental to society. This resulted in the government's repressive response, which immediately closed Tiktok Shop and prohibited it from operating. The main object of this study is a YouTube video from a channel named Ferry Irwandi. Ferry Irwandi's YouTube channel, precisely in the video content entitled